An exploration of how the alignment of business and information systems strategies is practiced by information systems managers in public service organisations - HOLOHAN, JAMES JOSEPH (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2018)
Strategic alignment (SA) remains a focus of attention for both research and practice alike, primarily because of its potential to contribute towards enhanced organisation performance. Today's challenge is not to achieve SA only when plans are devised, rather it is to continuously align IS and business goals. This places the focus on the 'how' rather than the 'what' of SA, thereby stimulating new lenses by which we can research SA. One such lens is the strategy-as-practice (SaP) lens which can elucidate practice, thus bringing a practice dimension to researching SA. With a paucity of research into SA within public service organisations (PSOs) and with the majority of studies concentrating on the role of senior executives, I decided to undertake an exploratory study to help understand how the alignment of business and IS strategies is practiced by IS managers in Ireland's Institutes of Technology (IIT). Therefore my study addresses the following research question: How is the alignment of business and IS strategies practiced by IS managers in IIT? To help inform my research, I developed a rich perspective on three supporting literature sets comprising the strategic management literature, the public service strategy literature and the literature on the role of the highest ranking IS executive. I undertook a systematic review of the SA literature. The review was carried out in a qualitative manner through the combination of a SaP lens and the constructivist grounded theory coding method. Ensuring consistency between my review of the SA literature, my research question and my methodological choices, I chose a research methodology that combines a SaP lens with the constructivist grounded theory coding method. The SaP lens I chose is Whittington?s (2006b) integrative framework for SaP. My choice of research design is case study, a design that has made valuable contributions to the field of IS theory and practice. Case study lacks guidance for data analysis, giving rise to practical limitations in terms of rigor and effectiveness. However, when data analysis is guided by Whittington?s (2006b) integrative framework for SaP and executed via the constructivist grounded theory coding method, the full benefits of applying case study as a research design can be realised. Based on certain criteria, I selected two Institutes of Technology as the appropriate setting within which to execute my study. A detailed explanation as to how I collected primary and secondary data is presented, as is the organisation of data in a case study database. My method of data analysis was underpinned by writing memos on the data I gathered and coding the content of these memos and interview data, in accordance with the code syntax I developed from the theoretical constructs within Whittington?s (2006b) integrative framework for SaP and the constructivist grounded theory coding method. Presentation of my case narratives comprises a single description of the national and sectoral context followed by a case narrative of each case at the macro, meso and micro levels. The intra-case and cross-case analysis are also presented in accordance with the macro, meso and micro level structure. The subset of analytical memos referring to the practices of the IS manager brought about the development of my mid-range theory in the form of a taxonomy. The taxonomy depicts the IS manager within IIT as a functional manager in receipt of a sector wide IS strategy, whose main concern is to obtain optimum efficiencies from IS at lowest possible cost. My study makes four key contributions to the body of knowledge that should be of interest to both academia and practice. The four key contributions are theoretical, practical, methodological and empirical. Finally, I conclude by summarising the findings from my study, its limitations and I propose avenues for further enquiry.
APPROVED
Keywords: Information Systems Strategy, Information Systems Manager, Ireland's Institutes of Technology, Case Study, Strategy as Practice